2019
DOI: 10.1111/trf.15481
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a routine hematology analyzer for quality control of leukoreduced plasma

Abstract: BACKGROUND: Quality control of residual white blood cells (WBCs) and red blood cells (RBCs) in leukoreduced plasma is mandatory. Although technological advances have been made, analysis of quality controls using routine hematology analyzers has not generally been introduced. The aim of this study was to evaluate if the routine hematology analyzer Sysmex XN-10, (Sysmex Nordic ApS) could be used for quality control of residual WBCs and RBCs in leukoreduced plasma. ABBREVIATIONS: CV = coefficient of variation; rR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Early studies, however, suggested that manual sample processing steps could inhibit introduction into routine automated QM processes 13 . A study that used the BF mode on the Sysmex XN‐10 analyzer concluded that it was suitable for rRBC counting in plasma at a level of 6000 RBCs/μL, but manual mixing was required and performance with PCs was not assessed 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies, however, suggested that manual sample processing steps could inhibit introduction into routine automated QM processes 13 . A study that used the BF mode on the Sysmex XN‐10 analyzer concluded that it was suitable for rRBC counting in plasma at a level of 6000 RBCs/μL, but manual mixing was required and performance with PCs was not assessed 15 …”
Section: Discussionmentioning
confidence: 99%
“…The Sysmex XN series of analysers (Sysmex Corp., Kobe, Japan) also includes an option for low‐level cell counting in BFs that has been reported as giving comparable results with microscopy, although limitations were noted with levels of RBCs in BFs less than 1000 cells/μL 14 . This analysis mode has also been described as being suitable for rRBC enumeration in leukoreduced plasma, with satisfactory performance at 6000 RBCs/μL, although it was unsuitable for counting residual white blood cells (rWBCs) 15 …”
Section: Introductionmentioning
confidence: 99%